Evaluation of the Activity of the Diatom Navicula Incerta Cultivated in Different Environments Against Several Species of Pathogenic Bacteria - Al-Jbory, M. J.; Al-Mayaly, I. K. (Iraqi Journal of Science, 2019)
Diatoms are considered a potentially new and valuable source of biologically active compounds including those with antimicrobial properties; so, this study was conducted to evaluate the antibacterial activity of Navicula incerta. The diatom was isolated from the salt water of Sawa Lake, southern of Iraq, it was cultivated in salt water then was adapted and cultivated in freshwater environment; the harvested and dried biomass was extracted, and the antibacterial activity of each extract was evaluated against several species of pathogenic bacteria. The chemical constituents of the extracts were also analyzed using Gas chromatography/Mass spectrometry technique. Generally, the result showed that fresh water extract of N. incerta has higher antibacterial activity than salt water extract; Furthermore, the diatom extract inhibited the growth of Staphylococcus aureus strain that was resistant to five different antibiotics; moreover, the chemical constituents of N. incerta in salt water were different from the same diatom when cultivated in fresh water.